2011
DOI: 10.1111/j.1365-2958.2011.07758.x
|View full text |Cite
|
Sign up to set email alerts
|

The cop operon is required for copper homeostasis and contributes to virulence in Streptococcus pneumoniae

Abstract: SummaryHigh levels of copper are toxic and therefore bacteria must limit free intracellular levels to prevent cellular damage. In this study, we show that a number of pneumococcal genes are differentially regulated by copper, including an operon encoding a CopY regulator, a protein of unknown function (CupA) and a P1-type ATPase, CopA, which is conserved in all sequenced Streptococcus pneumoniae strains. Transcriptional analysis demonstrated that the cop operon is induced by copper in vitro, repressed by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
211
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(229 citation statements)
references
References 57 publications
(94 reference statements)
16
211
0
2
Order By: Relevance
“…4C). It was shown recently that this operon could be transcriptionally induced by, and is sensitive to, toxic levels of copper sulfate (Shafeeq et al 2011), a phenotype which we confirmed (data not shown). Since S. pneumoniae is unlikely to encounter such nonphysiological levels of copper, our findings suggest that, instead, the operon is used to counter imbalances in divalent cation concentrations.…”
Section: Validation Of In Vitro Genotype-phenotype Relationships Leadsupporting
confidence: 78%
“…4C). It was shown recently that this operon could be transcriptionally induced by, and is sensitive to, toxic levels of copper sulfate (Shafeeq et al 2011), a phenotype which we confirmed (data not shown). Since S. pneumoniae is unlikely to encounter such nonphysiological levels of copper, our findings suggest that, instead, the operon is used to counter imbalances in divalent cation concentrations.…”
Section: Validation Of In Vitro Genotype-phenotype Relationships Leadsupporting
confidence: 78%
“…It is established that copper is an effective antimicrobial agent ex vivo, and there is evidence that it may play a similar role in vivo. Pathogens that lack copper efflux systems colonize poorly in the mammalian lung, possibly because of an inability to detoxify increased levels of copper in the host tissue (21). Detoxification of intracellular copper is achieved by efflux via P-type ATPase and RND (resistancenodulation-cell division) family efflux systems (22).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic bacterium Streptococcus pneumoniae contains the operon copY-cupA-copA, which encodes the repressor CopY, a protein of unknown function (CupA), and the copper-ATPase CopA (Shafeeq et al, 2011). Transcription of the cop operon is induced by copper and repressed by zinc, suggesting that the two metals compete for the same ligands in CopY.…”
Section: Streptococcus Mutans and Streptococcus Pneumoniaementioning
confidence: 99%
“…CopA is the major copper tolerance determinant in Streptococcus pneumoniae, while CupA is less important for copper defence. In addition to its role in copper homeostasis under free-living conditions, the cop operon is important for virulence (Shafeeq et al, 2011). Expression of the cop operon …”
Section: Streptococcus Mutans and Streptococcus Pneumoniaementioning
confidence: 99%